Clinical and cost impact of intravenous proton pump inhibitor use in non-ICU patients - Nasser, Soumana C. (2010)
AIM: To assess the appropriateness of the indication and route of administration of proton-pump-inhibitors (PPIs) and their associated cost impact. METHODS: Data collection was performed prospectively during a 6-mo period on 340 patients who received omeprazole intravenously during their hospital stay in non-intensive care floors. Updated guidelines were used to assess the appropriateness of the indication and route of administration. RESULTS: Complete data collection was available for 286 patients which were used to assess intravenous (IV) PPIs utilization. Around 88% of patients were receiving PPIs for claimed stress ulcer prophylaxis (SUP) indication; of which, only 17% met the guideline criteria for SUP indication, 14% met the criteria for non-steroidal-anti-inflammatory drugs-induced ulcer prophylaxis, while the remaining 69% were identified as having an unjustified indication for PPI use. The initiation of IV PPIs was appropriate in 55% of patients. Half of these patients were candidates for switching to the oral dosage form during their hospitalization, while only 36.7% of these patients were actually switched. The inappropriate initiation of PPIs via the IV route was more likely to take place on the medical floor than the surgical floor (53% vs 36%, P = 0.003). The cost analysis associated with the appropriateness of the indication for PPI use as well as the route of administration of PPI revealed a possible saving of up to $17 732.5 and $14 571, respectively. CONCLUSION: This study highlights the over-utilization of IV PPIs in non-intensive care unit patients. Restriction of IV PPI use for justified indications and route of administration is recommended.